Fair Wages in Employment: Islamic Insights into Aceh Province's Minimum Wage - Safrina, Lia; Hasanah, Uswatun (Malikussaleh Social and Political Reviews, 2023)
The problem of wages is more than just nominal. Other things are important to note, such as the time of payment and the wage component. Likewise, eligibility and fairness must be seen from the mechanism for determining it so that inequality between workers and job providers does not occur. The philosophy of wages as a form of worker protection is needed for government intervention to issue regulations made by the government by setting a minimum limit of salary/wages to be paid by the company to its workers. The Aceh government has set the Provincial Minimum Wage (UMP) to ensure wage equity between workers and job providers. This research is qualitative research that uses secondary data as a data source. The data used is Aceh Governor Regulation No. 560/1539/2022. The data was analyzed by describing the UMP setting system in Aceh and its relevance to the principles of justice, eligibility, and virtue. The results indicated that the setting of Aceh's minimum wage is relevant to the concept of wages in Islam and has fulfilled the principles of wages in Islam based on justice, eligibility, and virtue principles.